Práticas educativas do Movimento de Educação de Base – MEB: a alfabetização/conscientização de jovens e adultos pelas ondas do rádio (1961-1964) - Guedes, Kilma Cristeane Ferreira (2021)
The present study aims to analyze the educational practices and literacy strategies developed by Movimento de Educação de Base - MEB, that have promoted awareness and politicization of youth and adults belonging to the popular class, from 1961 to 1964. MEB emerged in a scenario of political and ideological effervescence in Brazil and in the world, having been created by Conferência Nacional dos Bispos do Brasil – CNBB, with Federal Government support, made official by Decree nº 50.370/1961. Its activities were implemented by the radio schools, using “radio waves” to promote the educational process, that teacher-speaker, monitor and students struggled to overcome the barriers of remote learning at this time. In 1963, Viver é Lutar booklet was adopted as a pedagogical support. MEB history, memory and legacy intertwine in the representations of its educational practices, however, it is pointed that, as long as the historical scenario had changed, they were sometimes overflowing, sometimes emptying. To understand this dynamism and the intricacies of these educational practices, this study focused on written and iconographic sources and, especially, those produced by MEB and its participants. The theoretical-methodological support was the study of Le Goff (1990), Halbwachs (1990), Nora´s (1993) Theory of Memory and the Theory of Representations by Chartier´s (1988, 1991) light, in dialogue with History of Youth and Adult Education and the studies of Paiva (2003), Freire (1967, 1987), Fávero (2004, 2006), among others. The analyzes pointed out contributions, contradictions and developments of these educational practices, configured as awareness/politicization strategies of the popular masses, that have collaborated until this time with the promotion of youth and adult education, confirming the importance of the MEB for Brazilian History of Education.